A pilot intervention to reduce burnout and enhance resilience through transcendental meditation among Georgetown University medical students - Chloé Jammes; Isaac Heiman; Hakima Amri (BMC Medical Education)
Abstract Background Rates of burnout, depression, and anxiety among healthcare workers are at historically high levels and have remained high in the aftermath of the COVID-19 pandemic. As aspiring physicians, medical students are the future of the healthcare profession. The practice of Transcendental Meditation (TM) has been shown to reduce burnout and stress in diverse populations, including healthcare professionals. To date, no data have been published on the benefits of TM for medical students. Our objective was to assess the efficacy of TM practice in reducing burnout and increasing resilience among medical students at Georgetown University School of Medicine (GUSoM) over three months between October 2022 and May 2023. Methods Forty-two GUSoM medical students qualified for and enrolled in the study. Thirty-nine students completed three months of TM training and practice, with the recommended regimen of meditating for 20 min twice a day. The students were assessed at baseline, one month, and three months using measures of burnout, depression, anxiety, insomnia, well-being, and resilience, of which burnout (emotional exhaustion) and resilience were the primary outcomes. Two-tailed paired-sample t-tests were used to determine the significance of changes in outcome measures over time. Results In the three-month post-test, significant changes were found for both primary outcomes, emotional exhaustion (p = 0.001, Cohen’s d effect size = -0.61) and resilience (p = 0.002, d = 0.53), as well as for anxiety (p < 0.001, d = -0.71), insomnia (p = 0.002, d = -0.53), depersonalization (p = 0.017, d = -0.40), depression (p = 0.006, d = -0.47), and mental wellbeing (p = 0.031, d = 0.36). TM practice compliance was high at 85%. Additionally, there were significant relationships between frequency of TM home practice and improvements in emotional exhaustion (p = 0.005), anxiety (p = 0.008), and insomnia (p < 0.001), and a marginally significant relationship with depression (p = 0.088). Conclusions These findings suggest that TM practice is an accessible, achievable, and effective intervention to decrease burnout and increase resilience for medical students. This study paves the way for future initiatives to evaluate a broad range of benefits of TM for medical students.